The pretence in education of people with profound intellectual and multiple disabilities - Kopeć, Danuta (Kultura-Społeczeństwo-Edukacja, 2020)
The phenomenon of pretence in the Polish educational system of the person with profound intellectual and multiple disabilities (PIMD) will be analized in the context of sociological concept of pretence by Jan Lutynski (1990). The subject of the study was the educational reality of the person with PIMD. Two main questions were formulated. What is the educational reality of the person with PIMD in the micro- and macrosystem context? What is happening in this educational reality? The study was conducted in interpretative paradigm based on quantitative research model using instrumental group case study. The subjects of the study were the people with PIMD (15) and school staff (57). During the study participant observertion, quantitaive deepened interview were used. The symptoms of pretence in education of the person with PIMD on the nmacrosystem level were visible in the form of inconsistencies in the legal acts regulating the course of education. On the microsystem level the manifestation of the pretence was the phenomenon of the “empty minutes” (i.e. time at school not used for the benefit of the person’s development). The results of the study on the macrosystem level suggest lack of the transparency of the legal acts. On the microsystem level the need of developing applicable standards in education of the people with PIMD.